Penerapan Digital Marketing Sebagai Strategi Pemasaran UMKM - Putri, Amalia Aisyah; Nurhadi, Nurhadi (Universitas Gajah Putih, Indonesia, 2023)
Community Activities in MSME activities that produce and sell various types of fried rice dishes in Surabaya.MSME nasgormumbol has been around for about 2 years, but its marketing uses conventional methods and is still minimal for digital marketing. Micro, Small, and Medium Enterprises (MSMEs) would greatly benefit from receiving guidance regarding the significance of incorporating digital marketing strategies into their marketing efforts.A system that can be utilized to attain sales objectives and facilitate improved operational endeavors.Furthermore, micro, small, and medium enterprises (MSMEs) are provided with guidance regarding strategies for optimizing and effectively managing their social media platforms.The outcome of the activity involves effectively managing social media accounts.The approach employed entails delivering training sessions accompanied by regular and impactful coaching to effectively bolster marketing endeavors of micro, small, and medium enterprises (MSMEs) with the aim of augmenting sales.